Effect of family communication patterns and peer relationships on cyber victimization and bullying: mediating effect of internet addiction - Aytaç, Özgenur; Uçan, Gülten; Baydur, Hakan (Journal of Dependence, 2022)
Objective: The aim of this study is to examine the effects of family communication patterns, peer relationships and internet addiction on cyber victimization and bullying and to evaluate the mediating effect of internet addiction through a model.Method: A total of 320 students between the ages of 14-19 studying in 8 high schools of 4 different types in Izmir province participated in the study. Sociodemographic information form, Revised Cyberbullying Inventory, Young Internet Addiction Scale, Peer Relationship Scale and Family Communication Patterns Scale were applied.Results: 49.9% of the participants were male with an average age of 16.25±1.13 years. 95.4% had a cell phone, 71.2% had a computer, and 42.5% had a tablet. The majority of the students (67.5%) can use the internet as much as they want without parental supervision and spend more than five hours a day on the internet (30.5%). In multivariate analysis, cyber victimization and internet addiction were significantly associated with peer, permissive and protective family type, while internet addiction was found to be associated with permissive and protective family type in cyber bullying. In the path analysis, the total effect of peer relationships and family communication on cyber victimization is β=0.212 and β=0.144, respectively. The total effect on cyberbullying was β=0.158 and β=0.138, respectively.Conclusion: Cyber victimization and bullying are influenced by peer relationships, family communication and internet addiction. The factors that cause internet addiction and thus cyber victimization and bullying in young people should be well identified and monitored together with the impact pathways.
Keywords: Cyber victimization and bullying; internet addiction; peer relations; family communication